The identity of Azara’s No. 315 “Ibiyau de cola extraña” and No. 316 “Ibiyau anónimo” (Aves: Caprimulgidae) - Smith, Paul (Zootaxa, 2017)
The identities of Azara’s No. 315 “Ibiyau de cola extraña” and No. 316 “Ibiyau anónimo”, and those of Caprimulgus sphenurus Vieillot, 1817 and C. epicurus Vieillot, 1817 which were based upon Azara’s descriptions, are elucidated. All are found to refer to the taxon currently known as Little Nightjar Setopagis parvula (Gould, 1837). A hitherto overlooked 20th Century usage of the name C. sphenurus by Bertoni (1900) validates this name, and hence, according to the ICZN code it could be correctly applied to this taxon. However, it is recommended that this name be suppressed in the interests of maintaining stability. New synonymies for this species are also clarified.